Variation in nutritive value of fodder maize (Zea mays) genotypes - Singh, Sultan; Katiyar, P K (The Indian Journal of Animal Sciences, 2012)
Genotypes (10) of maize (IG 96-2, -3, -4, -5, -6, -7, -11, -13, -14 and -15) were grown under uniform agronomic and soil conditions. Leaf and stem fractions were separated for each genotype and compared for chemical constituents, IVDMD and in-sacco DM, NDF and ADF disappearance. Leaf had double CP contents than stem fraction among the different genotypes. The CP contents varied from 3.72 to 12.82% in leaf and stem fractions. Organic matter, lignin and NDF, ash contents were higher in stem and leaf fractions, respectively. Leaf showed 8-10 units higher (P<0.05) IVDMD and IVDMD than stem fraction among the tested genotypes. Average IVDMD values were 66.34Â±0.33 in leaf vis-a-vis 57.54Â±0.66% in stem fraction. Within genotypes in-sacco disappearance of dry matter, NDF and ADF were significantly (P<0.05) higher in leaf than that in stem fraction. The present ill-sacco NDF and ADF disappearance ranged from 47.67 to 57.88% in leaf against 41.69 to 47.90 and 38.40 to 41.15% in stem fraction, respectively. Both fractions of IG 96 - 7 maize genotypes had significantly (P<0.05) higher IVDMD and in-sacco dry matter disappearance than other tested genotypes, while IG 96-7 maize genotypes had significantly (p<0.05) higher IVDMD and in-sacco dry matter disappearance than other tested genotypes, while IG 96-5 had the lowest (P